2017
DOI: 10.1017/s1041610217000734
|View full text |Cite
|
Sign up to set email alerts
|

Addenbrooke's cognitive examination-revised: normative and accuracy data for seniors with heterogeneous educational level in Brazil

Abstract: This study offers normative and accuracy parameters for seniors with lower education and it should expand the use of the ACE-R for this population segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 34 publications
0
48
0
16
Order By: Relevance
“…For example, the total mean ACE-R score for illiterate individuals was 45.9, while for elderly individuals with 12 or more years of education, the total mean score was 90.1, and this difference was reflected across all five domains. The study also found that the cutoff score to differentiate cognitively normal individuals from dementia in elderly individuals with less than five years of education was 55, while for more educated elderly individuals, it was 63 30 . A study carried out in Brazil with 167 elderly individuals reported that participants with lower education levels showed worse results for visual attention, reaction time, and learning skills.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, the total mean ACE-R score for illiterate individuals was 45.9, while for elderly individuals with 12 or more years of education, the total mean score was 90.1, and this difference was reflected across all five domains. The study also found that the cutoff score to differentiate cognitively normal individuals from dementia in elderly individuals with less than five years of education was 55, while for more educated elderly individuals, it was 63 30 . A study carried out in Brazil with 167 elderly individuals reported that participants with lower education levels showed worse results for visual attention, reaction time, and learning skills.…”
Section: Discussionmentioning
confidence: 81%
“…This is relevant, especially in developing countries where a significant number of older adults have limited education 23,29 . A study by César et al 30 evaluated 630 elderly Brazilians in an effort to provide ACE-R norms for seniors with different educational levels. They found that the scores in the separate ACE-R domains, and the total, varied significantly according to the educational level of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, studies with elder caregivers have revealed a close relation between burden and stress levels (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . The excessive burdens are defined as multi-dimensional answers to a negative care-related evaluation, while the perceived stress is the negative perception of a person regarding their daily life situations as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The general score varies from 0 to 100, and the highest the result, the better the cognitive function. In a Brazilian study who used a sample of elders from the community, the cut off point for this assessment was 65, with a sensibility of 75.6% and a specificity of 73.8% (10) . To our analyses, the same cut off point was used (65 points), and the reference was the group of elders who were caregivers and were below this point (current study Cronbach's alpha = 0.94).…”
Section: Methodsmentioning
confidence: 99%
“…MINI) to exclude any possible cognitive impairments or psychiatric pathologies. The resultsof the ACE-R were evaluated according to years of education 16. Individuals were excluded from the sample…”
mentioning
confidence: 99%